Breeding report of a new apple cultivar Yanjinyu - SUN Yanxia; TANG Yan; SONG Laiqing; LIU Daliang; ZHANG Xueyong; XU Xinxiang; ZHANG Shuo; LIU Xueqing; WANG Ping; ZHAO Lingling (Guoshu xuebao)
Yanjinyu is a mid ripe apple variety bred through a cross between Honglu and Guanghui made in 2008 in Yantai Agricultural Science Research Institute of Shandong Province, China. It was initially selected due to its bright yellow surface and good quality of the fruit. After six years of continuous observation, it was finally selected in 2020 and registered as a non major crop variety by the Ministry of Agriculture and Rural Affairs in 2024. The Yanjinyu tree was vigrous, with a wide open posture, high bud burst rate, and moderate branching ability. One year old branches were gray brown in color. The leaves were dark green. The leaf edge was sharply serrated. The flower bud was red, the petal was oblong and separated in relative positions. In Yantai area, the initial flowering period of Yanjinyu was mid April, the peak flowering period was from 17 to 19, April, and the fruit development period was about 130 days. The fruit was elliptical in shape. The fruit shape index was 0.95, and the average single fruit weight was 211.2 g; The fruit surface was smooth and rust free with bright yellow color. The flesh was light yellow, crispy, juicyand, aromatic. The aftertaste was sweet; The peel hardness of the fruit was 9.8 kg·cm-2, the soluble solids content was 14.8%, the titratable acid content was 0.22%, and the vitamin C content was 3.1 mg·100 g-1. The quality was excellent. Yanjinyu was susceptible to branch ring spot disease and rot disease, moderately resistant to apple glomerella leaf spot and rust diseases, highly resistant to winter cold, and moderately resistant to frost during flowering period. The shelf life of the fruit was 10-15 days. The fruits could be stored in cold store for 2 months. The variety could be suitable for free bagging cultivation. Intensive cultivation with dwarf rootstock should be recommended.